Notes on the genus Phlugiolopsis (Tettigoniidae: Meconematinae) with two new species from China - Zheng, Mengjia; Zhang, Tao; Shi, Fuming; Chang, Yanlin (Zootaxa, 2024)
In this paper, two new species of Phlugiolopsis are described, i.e. Phlugiolopsis hainanensis Zheng, Zhang, Shi & Chang sp. nov. and Phlugiolopsis cangshanensis Zheng, Shi & Chang sp. nov. and three synonyms are proposed as well. All examined specimens are preserved in the Museum of Hebei University.